A Study on Factors Affecting the Functioning of Janani Shishu Suraksha Karyakram in Ahmedabad District - Divya BharatKumar Barot; Arur Bhagyalaxmi (Medsci Publications, 2020)
Background: Every ﬁve minutes one woman somewhere in India dies due to pregnancy-related complications, amounting to one lakh maternal deaths and 10 lakh new-born deaths each year. The Janani shishu suraksha karyakram(JSSK)programme was launched to aid in endeavor of decrease in MMR by giving various entitlements to pregnant mother and children. Objective: To assess the factors affecting functioning of the Janani shishu suraksha karyakram program in community. Methodology: The cross sectional study was carried in Ahmedabad District out during the period of January 2014 to December 2015. The 235 beneficiaries were interviewed from the government health centers. Result: More than one third of beneficiaries were not aware about all the entitlements (benefits) of the programme.60% mothers had done USG in private set up. More than 70% mothers had to spend money for getting USG done followed by transport facility, medicine and laboratory investigations. Conclusion: The factors affecting functioning of JSSK program were out of pocket expenditure incurred during pregnancy. The beneficiaries have to spend money because of laboratory investigations, transport facility, medicines and complication etc.